Maize Inoculation with Azospirillum brasilense Ab-V5 Cells Enriched with Exopolysaccharides and Polyhydroxybutyrate Results in High Productivity under Low N Fertilizer Input - Oliveira, André L. M.; Santos, Odair J. A. P.; Marcelino, Paulo R. F.; Milani, Karina M. L.; Zuluaga, Mónica Y. A.; Zucareli, Claudemir; Gonçalves, Leandro S. A. (Frontiers in Microbiology, 2017)
Although Azospirillum strains used in commercial inoculant formulations presents diazotrophic activity, it has been reported that their ability to produce phytohormones plays a pivotal role in plant growth-promotion, leading to a general recommendation of its use in association with regular N-fertilizer doses. In addition, a high variability in the effectiveness of Azospirillum inoculants is still reported under field conditions, contributing to the adoption of the inoculation technology as an additional management practice rather than its use as an alternative practice to the use of chemical inputs in agriculture. To investigate whether the content of stress-resistance biopolymers would improve the viability and performance of Azospirillum inoculants when used as substitute of N-fertilizers, biomass of A. brasilense strain Ab-V5 enriched in exopolysaccharides (EPS) and polyhydroxybutirate (PHB) was produced using a new culture medium developed by factorial mixture design, and the effectiveness of resulting inoculants was evaluated under field conditions. The culture medium formulation extended the log phase of A. brasilense cultures, which presented higher cell counts and increased EPS and PHB contents than observed in the cultures grown in the OAB medium used as control. An inoculation trial with maize conducted under greenhouse conditions and using the biopolymers-enriched Ab-V5 cells demonstrated the importance of EPS and PHB to the long term bacterial viability in soil and to the effectiveness of inoculation. The effectiveness of liquid and peat inoculants prepared with Ab-V5 cells enriched with EPS and PHB was also evaluated under field conditions, using maize as target crop along different seasons, with the inoculants applied directly over seeds or at topdressing under limiting levels of N-fertilization. No additive effect on yield resulted from inoculation under high N fertilizer input, while inoculated plants grown under 80% reduction in N fertilizer showed yields at levels compared to fully fertilized plants, regardless the inoculation method. The presented data highlights the feasibility to partially substitute the N-fertilizer demand in non-legume crops using high-quality inoculant formulations, prepared with diazotrophic bacteria enriched with stress-resistance biopolymers that confer increased viability an effectiveness to the bacterial cells.